Pelatihan Penyusunan Modul Ajar sebagai Persiapan Implementasi Kurikulum Merdeka bagi Guru Pendidikan Anak Usia Dini - Sukarno, Sukarno; Ramadhika, Boris; Karma, Carolus Prima Ferri (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
A curriculum comprises objectives, materials, and content that are required to be studied in an academic institution in order to accomplish educational aims. As of now, the Merdeka Curriculum stands as the most recent educational framework with the potential to enhance the standard of instruction for children across the nation in Indonesia. However, optimal implementation of the Merdeka Curriculum has not yet occurred, particularly in early childhood education. The objective of this community service endeavor is to furnish early childhood teachers in Gunungpring, Magelang, with Merdeka Curriculum Training and its Practical Implementation. This activity was implemented through observation, implementation which consisted of training and mentorship, and evaluation. There were around 20 teachers from 10 schools who participated in this activity. It was done in the village hall of Gunungpring. The result of this activity was that the teachers’ skills and knowledge were enhanced in the Merdeka Curriculum for early childhood education. They claimed that the training and mentoring was successfully done to help them in increasing their knowledge of how the Merdeka Curriculum should be implemented. In addition, the teacher successfully developed Merdeka Curriculum-based Teaching Modules as the utilization of the results. They could manage to create modules which still focused on children playing and learning based on Merdeka Curriculum. The next step is to work with the local Education Department to offer additional training, particularly focusing on early childhood level. Additionally, the team intends to offer training in multimodal literacy. In the future, teachers will have additional references to improve their learning preparation.